Electronic Dance Music: From Deviant Subculture to Culture Industry - Conner, Christopher T.; Dickens, David R. (Lexington Books, 2023)
Electronic Dance Music: From Deviant Subculture to Culture Industry explores the subculture’s emergence as a deviant subculture. This text analyzes how industry professionals, fans, and public officials helped usher in a new age of EDM, arguing that while the defining features of the subculture made it attractive, they also laid the foundations for outsiders to commodify the movement as a culture industry. Conner and Dickens explore the concept of “commodified resistance” as the mechanism by which the movement's politically dissident features were removed and its place as a multi-billion-dollar industry made possible. Ultimately, this text advocates the continued utility of the culture industry thesis through an empirical analysis of the EDM subculture.